Construction of Narcotics Law Against Narcotics Abusers in Perspective Justice - Heru Pranoto; Adwani Adwani; Rizanizarli Rizanizarli; Mohd Gaussya (UIN Sunan Gunung Djati, 2024)
Article 54 of the Narcotic Drugs Act stipulates that drug abuse must undergo medical and social rehabilitation, but in fact, the provisions of Article 54 are not implemented to the maximum. This is evident from the existence of narcotic abusers who became non-rehabilitated addicts but dropped criminal penalties in prison. As a result, the agency is filled with excess capacity. The study's objectives are to investigate and evaluate the legal frameworks surrounding drugs law in order to fulfill the sense of justice towards drug abuse. This research is a normative law study, exploring legal thinking about the reconstruction of a fair law against drug abuse. To support data accuracy, legislative approaches, conceptual approaches, and comparison approaches are used. In normative legal research, data collection is carried out with library research and supplemented with field research. Data analysis is done qualitatively. The results of the research show that legal constructions that provide legal certainty, utility, and justice to drug addicts and drug users through a victim perspective, access to both social and medical rehabilitation, in addition to the trusts and purposes of the Narcotics Act, are ideal and coveted legislative constructions.